2013
DOI: 10.1007/s00221-013-3446-z
|View full text |Cite
|
Sign up to set email alerts
|

The learning of isometric force time scales is differentially influenced by constant and variable practice

Abstract: This experiment was set up to investigate the influence of constant and variable practice on performance accuracy and the time- and frequency-dependent structure of the force output dynamics in the learning of an irregular isometric force pattern. Traditional approaches to the variability of practice hypothesis have demonstrated benefits of task-induced variability at the outcome level of behavior, but there have been limited investigations of the effect of practice conditions on movement execution and particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Differences between constant practice and variable practice could perhaps be observed after longer practice periods and/or with a longer interval between the posttest and the retention test. Furthermore, the present study only evaluated the effects of task-induced variability at the goal level on participants' capacity to achieve a preselected goal after a practice period, based on the fact that previous studies reported a deleterious effect of task-induced variability when the transfer situation 25,26 or execution level 23 was evaluated. Nevertheless, effects of task-induced variability at the execution level (variable ways to perform SM) or in a transfer task condition (eg, a different or variable peak force) can also be relevant in SM training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between constant practice and variable practice could perhaps be observed after longer practice periods and/or with a longer interval between the posttest and the retention test. Furthermore, the present study only evaluated the effects of task-induced variability at the goal level on participants' capacity to achieve a preselected goal after a practice period, based on the fact that previous studies reported a deleterious effect of task-induced variability when the transfer situation 25,26 or execution level 23 was evaluated. Nevertheless, effects of task-induced variability at the execution level (variable ways to perform SM) or in a transfer task condition (eg, a different or variable peak force) can also be relevant in SM training.…”
Section: Discussionmentioning
confidence: 99%
“…These schemas consist in the development of relationships between a predefined goal and the parameters used to achieve this goal (retention situation) or a similar one (transfer situation). Consequently, effects of task-induced variability at the goal level (eg, varying force or velocity targets) or the execution level (ie, ways to achieve a given goal) have been studied in several motor skills, including tennis drive, 19 unimanual arm rotation, 20 manual aiming, 21,22 hand force production, 23,24 volleyball serve, 25 and shoulder adduction. 26 Although not consistent, 24 task-induced variability at the goal level typically results in lower accuracy and consistency, as measured by the absolute, 19,22 constant error, 19 or the root-mean-square jerk 20 immediately after the learning period.…”
Section: Introductionmentioning
confidence: 99%
“…The target pattern was characterized by a fractal dimension that consisted of frequency content from 0-12 Hz and exhibited a spectral slope (~1.5) between pink and brown noise. The wave form was constructed according to fractional Brownian motion (see King & Newell, 2013;). The target line mean was matched to 10 % of the participant's MVC, and the amplitude of the waveform was scaled to ±5 % of the participant's MVC.…”
Section: Methodsmentioning
confidence: 99%
“…During trials, participants were instructed to maintain a fixed position of the fingers, hand, and forearm against the table. The experimental setup was similar to King and Newell (2013).…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation